Outcomes after reversed corneal graft rejection: a report from the European VISICORT project - W John Armitage; Uwe Pleyer; Conor C Murphy; Derek Tole; Matthew D Griffin; Jesper Hjortdal; Katja C Iselin; Bertrand Vabres (BMJ Open Ophthalmology)
Objective This study aims to describe the outcome of corneal grafts, both low risk and high risk, after successfully reversed immunological rejection.Methods Datasets on reversed rejection episodes in penetrating and endothelial keratoplasties between 2014 and 2019 (n=876) were extracted from the Adverse Immune Signatures and their Prevention in Corneal Transplantation database, which contains the prospectively and consecutively collected corneal transplants from five European centres. Stratified by the preoperatively determined risk status for immunological rejection, the outcome parameters analysed included visual acuity, intraocular pressure, endothelial cell density and central corneal thickness before and after reversed rejection episodes.Results Fourty-seven (52%) out of a total of 91 identified rejection episodes were successfully reversed and were available for analysis (23 penetrating and 24 endothelial keratoplasties). No statistically significant change was found for any of the parameters studied between the values before and the values 3 months after the rejection episode, irrespective of the preoperative risk status.Conclusion The outcome of corneal grafts that survive immunological rejection may be clinically indistinguishable from the state before immunological rejection, irrespective of graft type and risk status. These findings support clinicians by providing information on prognosis after reversed rejection episodes and by giving patients realistic expectations regarding the outcome.